Complications of Monochorionic Diamniotic Twins: Stepwise Approach for Early Identification, Differential Diagnosis, and Clinical Management - Talita Micheletti; Elisenda Eixarch; Mar Bennasar; Josep María Martinez; Eduard Gratacos; Yang Pan (Wolters Kluwer Health, 2021)
Abstract. One in three monochorionic twins may develop complications during pregnancy. Monochorionic twins, especially monochorionic diamniotic (MCDA), present specific problems caused by the presence of interfetal placental anastomoses. The first critical step in the management of MCDA twins is identification in the first trimester. Secondly, close follow-up every 2 weeks is mandatory to allow early diagnosis and timely treatment of twin-twin transfusion syndrome. Other potentially severe complications include selective fetal growth restriction, twin anemia polycythemia syndrome or single fetal death. Thirdly, a correct differential diagnosis is critical to establish the best therapy. This may represent a clinical challenge since MCDA twin complications often overlap. A simple diagnostic algorithm may be of great help to establish the right diagnosis and management option. In this review we summarize the main steps for the clinical follow-up, differential diagnosis, and targeted management of MCDA twins complications.